Four-channel CWDM transmitter chip based on thin-film lithium niobate platform. (1st November 2022) - Chen, Kaixuan; Chen, Gengxin; Ruan, Ziliang; Fan, Xuancong; Zhang, Junwei; Gan, Ranfeng; Liu, Jie; Dai, Daoxin; Guo, Changjian; Liu, Liu
Abstract: Multi-lane integrated transmitter chips are key components in future compact optical modules to realize high-speed optical interconnects. Thin-film lithium niobate (TFLN) photonics have emerged as a promising platform for achieving high-performance chip-scale optical systems. Combining a coarse wavelength-division multiplexing (CWDM) devices using fabrication-tolerant angled multimode interferometer structure and high-performance electro-optical modulators, we demonstrate monolithic on-chip four-channel CWDM transmitter on the TFLN platform for the first time. The four-channel CWDM transmitter enables high-speed transmissions of 100 Gb/s data rate per wavelength channel (i.e., an aggregated date rate of 400 Gb/s).